Prognostic value of histamine H1 receptor expression in oral squamous cell carcinoma - Grimm, Martin; Krimmel, Michael Fred; Alexander-Friedrich, Dorothea; Munz, Adelheid; Kluba, Susanne; Keutel, Constanze; Hoffmann, Jürgen; Polligkeit, Joachim; Reinert, Siegmar; Hoefert, Sebastian (Clinical oral investigations, 2013)
Overexpression of the histamine H1 receptor (H1R) has been described in a variety of tumor models, but experience in oral squamous cell carcinomas (OSCC) is not available. Current adjuvant treatment options for OSCC can be improved by the identification of new targets of therapy. Herein, we evaluated H1R expression in a large patient cohort of OSCC.